Progressive Failure Analysis of Laminated Composite Plates With Two Serial Pinned Joints - Turan, Kadir; Kaman, Mete Onur; Gur, Mustafa (Taylor & Francis Inc, 2015)
This study presents experimental and numerical failure analyses for two serial pin loaded holes in unidirectional carbon fiber/epoxy resin composite laminates. The failure loads and failure modes of composite laminates are determined for different geometrical parameters and different stacking sequences. Three-dimensional ANSYS Parametric Design Language codes are developed in the ANSYS (R) finite element software. Hashin Failure Criteria and material degradation rules are used to determine failure loads and failure modes in the numerical analysis. Experimental and numerical results show that failure loads and failure modes were affected with geometrical parameters.
Keywords: progressive failure analysis; pinned joints; finite element method; laminated composites